Multilevel additive-multiplicative model of generalized indicators assessment on the basis of balanced scorecard strategic management - Stepanuk, M.Y. (PROBLEMS IN PROGRAMMING, 2025)
The problem of generalized indicators assessment on the basis of balanced scorecard strategic management is considered. The multilevel additive-multiplicative model of generalized indicators assessment of balanced scorecard is proposed. The proposed model appears to be easy to use and makes it possible to boost the adequacy of assessments, which are used in strategic management.Problems in programming 2010; 1: 108-115